Focal Cortical Dysplasia: Diagnosis, Classification, and Treatment Options - Pizzo, Francesco; Fichera, Valeria; Zanghì, Antonio; Praticò, Andrea D.; Vecchio, Michele; Falsaperla, Raffaele; Lavalle, Salvatore; Marino, Francesco; Palmucci, Stefano; Belfiore, Giuseppe; Polizzi, Agata (Journal of Pediatric Neurology, 2024)
Focal cortical dysplasias (FCDs) include a spectrum of anomalies of cortical development that consist in one or more areas with altered lamination and in some cases, neurons of abnormal morphology. Clinically, these structural anomalies led to arise of epilepsy, which is more often a focal, drug-resistant type with onset in pediatric or adolescent age. Occasionally, other symptoms have been reported in patients with FCDs, such as headache, movement disorders, and cognitive impairment. According to International League against Epilepsy scheme of 2011, three main subtypes of FCD can be distinguished, based of anatomopathological feature, radiological signs, and clinical expression. Magnetic resonance imaging (MRI), fluorodeoxyglucose positron emission tomography, and neurophysiology are the cornerstones of diagnosis, although their negativity cannot exclude FCD in symptomatic patients, especially in FCD type I which often is elusive. In MRI, the main finding is the irregularity of the cortical–subcortical signal, specifically reduction of cortical thickness and absence of clear demarcation between gray and white matters, which is strongly diagnostic for FCD. Epilepsy related to FCD is difficult to manage and until now there is not a clear direction for treatment's rules. FCD shows poor response to antiepileptic drugs (AEDs), and there is no evidence of some AED that has proved more efficacy than others in patients with FCDs. Considering genetical and pathophysiological recent acquisitions, mammalian target of rapamycin inhibitors may play a fundamental role in future treatment of FCDs, but nowadays, surgery still remains the main weapon, with 50% of patients who undergo neurosurgery.
Keywords: focal cortical dysplasia; migration defects; neurons; genetic